Implant survival rate and prosthetic complications of full-arch implant-supported fixed prostheses In edentulous upper jaws : a cohort study = Tasa de supervivencia de los implantes y complicaciones protésicas de las prótesis fijas soportadas por implantes de arcada completa en maxilares superiores edéntulos : un estudio de cohorte - Reda, Rodolfo
Full-arch implant-supported fixed dental prostheses, an implant-supported prosthesis, which the patient must carefully manage in home oral hygiene procedures, is the fixed alternative to a mucosal-supported or implant-anchored prosthesis. Clinically, the execution of this rehabilitation requires four implants for the lower jaw and six implants for the upper jaw. The aim of the present study is to verify the survival-rate of implants for implant-fixed prostheses in the edentulous upper jaw. This retrospective study was carried out on patients who received an upper full-arch fixed prostheses on six implants for rehabilitation. A total of 36 patients were included and evaluated from a clinical and radiographical point of view. The follow-up period in which the data were collected on the upper full-arch is between 60 and 84 months. A total of 232 implants were inserted and monitored in this period. Clinical and radiographic evaluations were carried out on all 232 implants, with constant re-evaluation. The total implant survival rate is 93.1%, a value which is similar to previous studies already published on the topic. There were few prosthetic complications, mainly the fracture of anterior prosthetic teeth. Most of these full-arch, which as antagonist had another previously made full-arch implant-supported fixed dental prostheses or overdenture on four or overdenture on two implants, achieves good results in this study at 84 months.